The physics handbook : fundamentals and key equations - Poole, Charles P. (John Wiley & Sons, 1998)
This book contains many concepts involving Lagrangians, parity, dispersion relations, chaos, free energies, statistical mechanical ensembles, and elementary particle classifications, and these materials are apread throughout the remainder of the chapters.